Design and Development of a Website Crew E-Recruitment System in Improving Recruitment Chart at PT. Equinox Bahari Utama - Hariyanti, Retno; Sengadji, K. G.; Praugusta, M. A. P (RSF Conference Series: Engineering and Technology, 2023)
The effectiveness of recruitment and selection is a benchmark for the company's success which lies in its quality if the availability of the number of Human Resources supports and is sufficiently qualified and professional. PT. Equinox Bahari Utama is one of the companies engaged in crew management. The importance of media as a means of recruitment that takes place at PT. Equinox Bahari Utama can be used as the basis of increasing the quality of the company in order to make the company a reference for shipping companies in Indonesia. In this study, the author uses research and development methods that include designing or building a system that supports research. In addition, at the analysis stage researchers use descriptive qualitative analysis that uses observation. The e-recruitment system that was built is a system that aims to find out how to develop crew management system applications to improve the efficiency and effectiveness of the recruitment process that takes place at PT. Equinox Bahari Utama. And also in order to be able to help the staff of PT. Equinox Bahari Utama in carrying out the recruitment process required from the shipowner. With various requirements and a series of recruitment processes, the existence of this system is expected to increase the efficiency of the ongoing recruitment process.